The Duality of Place in Emily Nasrallah's Novel "A Cat’s Diaries" - Farid, Zahra (Al-Adab Journal, 2019)
The element of place and its employment within the structure of fiction is one of the most important elements and techniques in contemporary novels, especially in the novels on the subject of war. Wars often occur to control the territory of the adversary. The novels that shed light on war and its effects such as destruction, murder and migration, focus on Place as a key element. This study aims at addressing the issue of Place and its dualities in Emily Nasrallah's novel "A Cat’s Diaries" (1931-2018), the writer of woman, war and migration, which studies the war and its impacts in this novel from a completely different point of view. It deals with the story of the homeless cats and their fate during the war and their relations with the people, in particular, the boys, from the tongue of special narrator that is a cat named "Ziko"One of the most important findings of this study is that the real setting in this novel is distributed between the interior and the exterior, according to the sense that is conveyed to the people in it. Open places are not constant sources of happiness, and the place can share its roles among itself, depending on its population's sense of place. The place has been employed in fiction and its relationship to personalities, to represent the material and spiritual losses that affected it and its residents, and to express human relations in the disasters that were experienced by ordinary combatants and ordinary people, as well as by animals in the midst of the Lebanese civil war.